Investigation of personality characteristics of hearing impaired athletes participating in 2nd European youth hearing impaired athletics championships - Erdal Demır; Kursad Sertbas; Mustafa Vural; Ugur Senturk (Türk Spor ve Egzersiz Dergisi)
The aim of this research is to assess the personality characteristics of national hearing impaired athletes and to evaluate the relationship between gender and branches with the personality characteristics. For this purpose, this research has been designed on screening model. The research was performed with Athletes Participating in 2nd European Youth Hearing Impaired Athletics Championships, held on 21-23 August 2014 inTrabzon. The research group consisted of 67 athletes including 26 fromTurkey, 2 fromBelgium, 3 fromEstonia, 8 fromGermany, 4 fromLithuania, 1 from theNetherlands, 12 fromPoland, 9 fromRussiaand 2 fromSpain. 34.3% (n = 23) of athletes were female, 65.7% (n = 44) consisted of male athletics. PERI (Personality Inventory) personality scale consisting of 25 items was used for measuring personality traits of national hearing impaired athletes in the research. PERI; is composed of 5 subgroups including openness to experience, sense of responsibility, extraversion, compatibleness and emotional stability. The scale was applied with face to face technical to athletes by two experts who know the language of the hearing impaired. In the analysis of the research data, frequency and percentage distribution, t-test, Kruskal-Wallis test and Mann-Whitney U tests were performed. In the result of the research; There were no significant differences between sport branches and gender and personality characteristics of the athletes. (p gt;0.05). National hearing impaired athletes had in ''not effective or low'' level the personality trait of emotional stability and they defined as the individuals not feeling optimistic enough, easy-tempered and having a high level of anxiety. But they had in ''effective or high'' level the personality traits of sense of responsibility and they defined as disciplined individuals who do not give up in the face of difficulties themselves, pay attention to details, are planned in everything they do.